2017
DOI: 10.1016/j.jvs.2017.03.435
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategy based on the natural course of the disease for patients with spontaneous isolated abdominal aortic dissection

Abstract: Based on our observation, the majority of symptomatic and asymptomatic SIAAD patients can be managed conservatively unless they present with aortic rupture, concomitant large aortic aneurysm, or underlying connective tissue disease. However, a more proactive management strategy may be required for female, symptomatic patients or those with suprarenal SIAAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…2. During follow up, other than two deaths before treatment and 35 deaths in the Kang et al 13 study with non-separated data, 21 deaths The overall 91% of IAADs were spontaneous, which is comparable to previous studies reporting dissection types (66.7e100%). 3,7,9,11,14,18,19,21,25,26 Hypertension, smoking, and hyperlipidaemia were the most common concomitant risk factors of IAAD, which could induce endothelial damage and a persistent inflammatory response to stimulate formation of atherosclerosis and spontaneous aortic dissection.…”
Section: Clinical Outcomessupporting
confidence: 71%
See 4 more Smart Citations
“…2. During follow up, other than two deaths before treatment and 35 deaths in the Kang et al 13 study with non-separated data, 21 deaths The overall 91% of IAADs were spontaneous, which is comparable to previous studies reporting dissection types (66.7e100%). 3,7,9,11,14,18,19,21,25,26 Hypertension, smoking, and hyperlipidaemia were the most common concomitant risk factors of IAAD, which could induce endothelial damage and a persistent inflammatory response to stimulate formation of atherosclerosis and spontaneous aortic dissection.…”
Section: Clinical Outcomessupporting
confidence: 71%
“…1. Among the included studies, four were retrospective cohort studies 3,13,14,20 and the rest were case reports or case series. Ten studies reported different treatment strategies, including conservative treatment, ENDO and OS 3,7,8,10,13,15e18,26 ; six studies only reported ENDO 9,14,19e21,25 and one study only reported OS.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations